PENGEMBANGAN ALAT EVALUASI LATIHAN SOAL BERBASIS EDUCANDY PADA MATERI WAWANCARA - Shafa Nabila Sulistio Putri; Elly Sukmanasa; Yudhie Suchyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted at Kedunghalang 3 State Elementary School, in the even semester of the 2024/2025 academic year. The method in this research uses the Research and Development (R&D) method with the development of the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. This research involved 32 students and carried out a validation process and trial evaluation of the learning that had been developed. Validation was carried out by four validation experts, namely media experts, language experts, material experts (lecturers), and material experts (teachers). Based on the validation results carried out by the validator, the results obtained were 100% media expert, 100% language expert, 90% material expert (lecturer), and 87.2% material expert (teacher), with an average result of 92.5% which is included in the